2018
DOI: 10.1371/journal.pone.0208053
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of drug-susceptibility patterns and gene sequences associated with clarithromycin and amikacin resistance in serial Mycobacterium abscessus isolates from clinical specimens from Northeast Thailand

Abstract: Mycobacterium abscessus is an important infectious agent highly associated with drug resistance and treatment failure. We investigated the drug resistance situation of M. abscessus in Northeast Thailand and the possible genetic basis for this. Sixty-eight M. abscessus clinical isolates were obtained from 26 patients at Srinagarind Hospital during 2012–2016. Drug susceptibility tests and sequencing of erm(41), rrl and rrs genes were performed. Mycobacterium abscessus was resistant to 11/15 antibiotics (nearly 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 39 publications
1
29
1
2
Order By: Relevance
“…When the antimicrobial resistance rates obtained in the present study were compared with the results of previous studies, we found that there were high rates of resistance to multiple antimicrobials among the three MABC subspecies. The resistance rates regarding fluoroquinolones (CIP and MXF) and other broad-spectrum antibiotics (such as DOX, SXT, and MIN) were similar (all >70%) to those previously reported for MABC isolates in Taiwan Province of China, 23 as well as in Japan, 24 Thailand, 25 the USA, 26 and France. 27 In contrast, the rate of IPM resistance varied significantly among different studies.…”
Section: Discussionsupporting
confidence: 82%
“…When the antimicrobial resistance rates obtained in the present study were compared with the results of previous studies, we found that there were high rates of resistance to multiple antimicrobials among the three MABC subspecies. The resistance rates regarding fluoroquinolones (CIP and MXF) and other broad-spectrum antibiotics (such as DOX, SXT, and MIN) were similar (all >70%) to those previously reported for MABC isolates in Taiwan Province of China, 23 as well as in Japan, 24 Thailand, 25 the USA, 26 and France. 27 In contrast, the rate of IPM resistance varied significantly among different studies.…”
Section: Discussionsupporting
confidence: 82%
“…Specifically, M. abscessus subsp. abscessus and M. bolletii might harbour a functional gene erm(41) leading to lack of efficacy of macrolide; therein, raising questions on the utility of clarithromycin in the treatment of infections caused by these microorganisms with inducible macrolide resistance [18,27,28]. To investigate for this probability, gene sequencing is advisable.…”
Section: Discussionmentioning
confidence: 99%
“…e same issue emerged also for imipenem. Being so, while a prolonged incubation is recommended to test clarithromycin in vitro activity [19,29,30], a long incubation time can cause the inactivation of other antibiotics such as imipenem [28,30]. In light of this, the reported results might have been misleading.…”
Section: Discussionmentioning
confidence: 99%
“…Currently there are no interpretative breakpoints available for meropenem, ertapenem and doripenem antibiotics for which those related to imipenem are considered [29]. Breakpoints for tigecycline were based on those used by Ananta [30].…”
Section: Methodsmentioning
confidence: 99%